Prevalence and Cost Analysis of Complex Regional Pain Syndrome (CRPS): A Role for Neuromodulation. Issue 5 (29th September 2017) - Elsamadicy, Aladine A.; Yang, Siyun; Sergesketter, Amanda R.; Ashraf, Bilal; Charalambous, Lefko; Kemeny, Hanna; Ejikeme, Tiffany; Ren, Xinru; Pagadala, Promila; Parente, Beth; Xie, Jichun; Lad, Shivanand P.
Abstract : Objective: The diagnosis and treatment of complex regional pain syndrome (CRPS) is challenging and there is a paucity of data describing its overall cost burden and quantifying its impact on the US healthcare system. The aim of this study was to assess the prevalence and healthcare utilization costs associated with CRPS. Materials and Methods: A retrospective longitudinal study was performed using the Truven MarketScan® database to identify patients with a new indexed diagnosis of CRPS (Type I, II, or both) from 2001 to 2012. We collected total, outpatient, and pain prescription costs three years prior to CRPS diagnosis (baseline), at year of CRPS diagnosis, and eight‐year post‐CRPS diagnosis. A longitudinal multivariate analysis was used to model the estimated total and pain prescription cost ratios comparing patients diagnosed before and after CRPS. Results: We included 35, 316 patients with a newly indexed diagnosis of CRPS (Type I: n = 18, 703, Type II: n = 14, 599, Unspecified: n = 2014). Baseline characteristics were similar between the CRPS cohorts. Compared to two‐ and three‐year baseline costs, one‐year prior to diagnosis for all CRPS patients yielded the highest interquartile median [IQR] costs: total costs 7904[3469, 16, 084]; outpatient costs 6706[3119, 12, 715]; and pain prescription costs 1862[147, 7649] . At the year of CRPS diagnosis, the median [IQR] costs were significantly higher than baseline costs: total costs 8508[3943, 16, 666] ; outpatient costs 7251[3527, 13, 568] ; and pain prescription costs 2077[140, 8856] . Over the eight‐year period after CRPS diagnosis, costs between all the years were similar, ranging from the highest (one‐year) to lowest (seven‐years), 4845 to 3888. The median total cumulative cost 8‐years after CRPS diagnosis was 43, 026 and 12, 037 for pain prescription costs. [Correction added on 06 November 2017 after first online publication: the preceding sentence has been updated to demonstrate the median cumulative cost in replacement of the additive cumulative mean costs.]. During the CRPS diagnosis period, patients are expected to have a total cost 2.17‐fold and prescription cost 2.56‐fold of their baseline cost annually. Conclusions: Our study demonstrates that there is a significant increase in cost and healthcare resource utilization one‐year prior to and around the time of CRPS diagnosis. Furthermore, there is an increased annual cost post‐diagnosis compared to baseline costs prior to CRPS diagnosis.